Graphic angle measure as an electrocochleography evaluation parameter - Lopes,Karen de Carvalho (2011)
To improve electrocochleography's diagnostic sensitivity in Meniére's disease - new assessment methods are being studied. AIM: To determine whether or not graphic angle measurement is sensitive and specific to Menière's disease laboratorial diagnosis and if there is an increase in the electrocochleography's sensitivity and specificity when graphic angle measurements are associated with Summating Potential-Action Potential ratio (SP/AP ratio). METHODS: Electrocochleography's was used to analyze 71 ears from 55 subjects: 41 patients with clinical diagnosis of Menière's disease (MD group), and 14 healthy individuals as control (Group C). Graphic results were analyzed initially to obtain the SP/AP ratio; afterwards, through another program graphic angle measurements were calculated. RESULTS: Sensitivity and specificity values of angle measures, SP/AP ratio, and the association between them varied according to the cutoff point, the highest equilibrium between sensitivity and specificity was observed with the values of 166.25 for angle measurement and 27% for SP/AP relation; 62.79% / 60.71% and 74.42% / 67.86%, respectively. The association between measurements showed a sensitivity increase due to the specificity decrease; 88.37% and 50%, respectively. CONCLUSION: Angle graphic measurement is not sensitive and specific enough for the laboratorial diagnosis of MD. Angle graphic measurement and SP/AP ratio association proved to be higher in sensitivity, in detriment of exam specificity.